Porous Poly(vinylidene fluoride-co-hexafluoropropylene)/copper oxide nanocomposite membranes for piezoelectric strain sensing - Maryam Al-Ejji; Tamanna Promi; Farah Sangor; Zinab Al-Awa; Sumalatha Bonthula; V. Radhika; Deepalekshmi Ponnamma (Discover Applied Sciences)
Abstract The emerging field of porous piezoelectric strain sensors attracted a wide range of applications in healthcare monitoring, wearable electronics, and other dynamic applications due to their durability, high sensitivity, and real-time monitoring. This study presents the development of porous poly (vinylidene fluoride-co-hexafluoropropylene) (PVDF-HFP)/copper oxide (CuO) nanocomposite membranes for piezoelectric strain sensing. The morphology and the dispersion of CuO nanoparticles and nanofibers in PVDF piezoelectric films with different nano-CuO contents are studied by X-ray diffraction, Fourier transform infrared spectrum, scanning electron microscopy and dielectric studies. The PVDF-HFP acts as a scaffold, allowing ions to flow within the porous percolated channels, resulting in a highly robust membrane with desired dielectric properties. The DMA studies enhanced the strain sensing performance of the 3.5 and 7 wt.% CuO nanofibers loaded with PVDF-HFP membranes compared with the 3.5 and 7 wt.% CuO nanoparticles and pristine membranes. The dielectric properties of the composites also showed high storage values for the CuO/PVDF-HFP samples compared to the pristine polymer. Moreover, the surface water contact angles of the membranes have slightly increased after loading the nanomaterial into the PVDF-HFP matrix, which strongly influenced the surface energies, indicating hydrophobicity. The current study, thus, demonstrates the piezoelectric strain sensing devices made from PVDF-HFP/CuO nanofibers for humid atmospheres. Graphical Abstract